2012
DOI: 10.28945/1679
|View full text |Cite
|
Sign up to set email alerts
|

Measuring System Performance & User Satisfaction after Implementation of ERP

Abstract: Now a day ERP systems are being adopted by various organizations as part of their business growth strategies. However, one must realize that implementation of an ERP system is not a goal but a journey towards the goal. Even after successful implementation, the goal is not achieved until the system is completely used. The satisfaction of the users and the overall performance must be measured periodically to evaluate the success of the implementation and the overall object of having the Enterprise level of Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Measuring the performance of any activity/process is the basis of governance, so there is no doubt that this CSF deserves a much higher degree of engagement. This observation fully coincides with the results of some recent studies, such as (Sun et al, 2015); (Shatat, 2016) and (Batada & Rahman, 2012).   Besides CSF9, which was rated as very poorly implemented in both sectors, other CSFs that were identifi ed as particularly challenging for one of the sectors include: "Completed feasibility study" (CSF1) in the private sector and "Use of steering committee for project activity control" (CSF17) in the public sector.…”
Section: Discussion and Practical Contributionsupporting
confidence: 93%
“…Measuring the performance of any activity/process is the basis of governance, so there is no doubt that this CSF deserves a much higher degree of engagement. This observation fully coincides with the results of some recent studies, such as (Sun et al, 2015); (Shatat, 2016) and (Batada & Rahman, 2012).   Besides CSF9, which was rated as very poorly implemented in both sectors, other CSFs that were identifi ed as particularly challenging for one of the sectors include: "Completed feasibility study" (CSF1) in the private sector and "Use of steering committee for project activity control" (CSF17) in the public sector.…”
Section: Discussion and Practical Contributionsupporting
confidence: 93%
“…Enterprise value-adding processes Shaqrah and Al Maliki (2018) concluded that enterprise systems implementation area complex process, particularly when using new knowledge through the implementation phase. Batada and Rahman (2012), Rouhani et al (2017) measured ENTVA by using a balanced scorecard model focusing on the internal business process and highlighting the operational efficiency of business processes in enterprises. Azhdari et al (2012) emphasized attaining ENTVA systems by maintaining a knowledge mechanism through standardization, formalization and specialization commitment.…”
Section: Vjikms 531mentioning
confidence: 99%
“…The importance of differentiation within systems enables the providers to adjust system features to user needs which studies indicate have a direct affect on value perceptions ( Cort et al, 2007 ). Similarly, the potential of systems to enable inter-operability through integration between disparate systems brings enhanced benefit to inter-departmental working ( Batada and Rahman, 2012 ). An intuitive system design reduces the effort for users to complete tasks ( Mikkelsen et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the absence of software enhancements has resulted in speed issues from memory leaks, unreleased locks, non-terminated threads, shared-memory and storage fragmentation ( Zhao and Wu, 2013 ). The importance of adequate support structures is a prerequisite for the positive measurement of user satisfaction in the context of enterprise resource planning ( Batada and Rahman, 2012 ).…”
Section: Discussionmentioning
confidence: 99%